The Influence of Technological Knowledge Base and Organizational Structure on Technology Collaboration - Zhang, Jing; Baden‐Fuller, Charles (Journal of Management Studies, 2010)
abstractThis study investigates how an incumbent company's internal characteristics influence its propensity to form learning alliances. A firm may be reluctant to enter a research alliance when it has deep knowledge in a certain technological field due to concerns about knowledge leakage and the low possibility of being able to learn much from collaboration. On the contrary, when the firm has a broad knowledge base, it may have high propensity to enter alliances due to more self‐confidence in its ability to learn fast from partners. In addition, we argue that when a firm concentrates its R&D at a central location, this neutralizes the positive and negative influences of the two knowledge base features on alliance formation. We tested and found support for the hypotheses using a database of 1550 alliances undertaken by 78 large incumbent pharmaceutical, chemical, and agro‐food companies active in the biotechnology sector during 1993–2002.